Assessment of oral mucosal condition and periodontal status of the institutionalized elderly living in geriatric homes of Dakshina Kannada District, Karnataka, India - R Pandya Sajankumar; Vijaya Hegde (Wolters Kluwer Medknow Publications, 2019)
Background: It is recognized that in developing countries like India, institutionalized health care is expensive. Thus, individual residing in geriatric homes have a higher rate of oral disease. To promote the oral health of the elderly, we need to know the oral mucosal condition and periodontal status. Aim: The aim of this study is to assess the oral mucosal conditions and periodontal status of the institutionalized elderly living in geriatric homes. Material and Methods: A cross-sectional survey was conducted in geriatric homes of Dakshina Kannada district. The sample size was estimated to be 384. The WHO oral health assessment pro forma (1997) was used to collect the data. The American Dental Association Type III examination method was used. The data obtained was coded and fed into the Statistical Package for the Social Sciences (Chicago, IL, USA) version 16.0 for analysis. Differences in proportions were compared using the Chi-squared test. Results: In terms of oral mucosal conditions, 13.80% and 16.15% of the total study participants had oral submucous fibrosis and denture stomatitis, respectively. On periodontal examination, 1.82% of participants had bleeding on probing. Calculus was present in 21.36% of participants. 49.47% of study participants had pocket depth measuring 4-5 mm. Conclusion: The present study concludes that oral mucosal condition and periodontal status are poor in the institutionalized elderly living in geriatric homes of Dakshina Kannada district.